2000
DOI: 10.1046/j.1365-3008.2000.00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and abundance of the Amami rabbit Pentalagus furnessi in the Amami and Tokuno Islands, Japan

Abstract: The Amami rabbit Pentalagus furnessi is a rare forest‐dwelling form endemic to the Amami and Tokuno Islands in Japan. In order to estimate the distribution and abundance of the Amami rabbit we counted their faecal pellets along forest roads and streams as well as within the forests on Amami and Tokuno Islands during January 1993–March 1995. The number of pellets/km along a stream gave a practical index for measuring relative abundance. The rabbit was estimated to be distributed over about 370 sq km on Amami Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Takatsuki (1986) also found that although M. sinensis was an abundant species on Mount Goyo (39°05′N, 141°42′E) in Iwate Prefecture, it was only partly grazed by C. nippon and only comprised 2% of their fecal composition. Sugimura et al (2000), however, observed numerous feeding signs on M. sinensis by Pentalugus furnessi (Amami rabbit), which is an endemic species to the Amami (28°17′N, 129°22′E) and Tokuno (27°46′N, 128°57′E) Islands of Japan. Although not entirely conclusive, M. sinensis may not be a preferred source of forage for wild ruminants in potential production regions of the crop, but might be suitable for smaller mammals.…”
Section: Biotic Interactions Of M Sinensismentioning
confidence: 99%
“…Takatsuki (1986) also found that although M. sinensis was an abundant species on Mount Goyo (39°05′N, 141°42′E) in Iwate Prefecture, it was only partly grazed by C. nippon and only comprised 2% of their fecal composition. Sugimura et al (2000), however, observed numerous feeding signs on M. sinensis by Pentalugus furnessi (Amami rabbit), which is an endemic species to the Amami (28°17′N, 129°22′E) and Tokuno (27°46′N, 128°57′E) Islands of Japan. Although not entirely conclusive, M. sinensis may not be a preferred source of forage for wild ruminants in potential production regions of the crop, but might be suitable for smaller mammals.…”
Section: Biotic Interactions Of M Sinensismentioning
confidence: 99%
“…The droppings of the rabbit P. furnessi were counted along streams and forest roads across the whole study area (Sugimura et al, 2000; Sugimura & Yamada, 2004; Japanese Ministry of the Environment, unpubl. data).…”
Section: Methodsmentioning
confidence: 99%
“…Eleven endemic mammal species including those in families Soricidae, Hipposideridae, Vespertilionidae, and Leporidae (Yamada ) and a subspecies of wild boar ( Sus scrofa ) live on Tokunoshima Island as relict species from the Eurasian Continent. The Amami rabbit is the only rabbit species and one of the relict species endemic to the Ryukyu archipelago and lives only on Tokunoshima Island and Amami Ohshima Island, Japan (Sugimura et al ). The Amami rabbit mainly lives in forested areas and is thought to have low mobility because of its small home range (1.3 ha for males and 1.2 ha for females; Yamada et al ).…”
Section: Study Areamentioning
confidence: 99%